On Parametric Surfaces with Constant Mean Curvature Along Given Smarandache Curves in Lie Group - Yuzbasi, Zuhal Kucukarslan; Taze, Sevinç (My University, 2022)
This paper finds sufficient conditions to determine a surface whose mean curvature along a given Smarandache curve is constant in a three-dimensional Lie group. This is accomplished by using the Frenet frames of the specified curve to express surfaces that span the TN, NB, and TB Smarandache curves parametrically. In terms of the curvatures of given Smarandache curves, marching scale functions, and their partial derivatives, the mean curvatures of these surfaces along the given TN, NB, and TB Smarandache curves are determined. Sufficient conditions are found to maintain the provided mean curvatures of the resulting surfaces at a constant value. Finally, some examples are provided.
Keywords: Mean curvature; Lie group; Smarandache Curve